A study on the challenges faced by Maybank in the uses of M‐Commerce in Malaysia / Khuzaireeq Khamarudin and Noreimie Mohamad - Khamarudin, Khuzaireeq; Mohamad, Noreimie (Faculty of Business and Management, 2013)
Mobile commerce (m-commerce) is one of the latest payment method and business transaction activities in Malaysia that now is being practically use by every organization in improving their business system. The issue that we are going study is either m-commerce method is generally having any challenges or not to some of organization that implement this method. This paper aims to (1) Identify what are the elements that is involve to the challenges of m-commerce; (2) Examine the level of strength for each element that involve. The purpose of the study is to analyse the gap between theories in each element that we identified; (1) Mobile client, (2) Communication infrastructure, (3) Security and (4) Consumer’s Trust. We have interview Maybank Malacca branch executive, Maybank main executive Kuala Lumpur and user of m-commerce and they all agree that Malaysia still have a problem toward these element. This paper will investigate the challenge and barriers towards this problem.